Achieving full connectivity of sites in the multiperiod reserve network design problem. (May 2017) - Jafari, Nahid; Nuse, Bryan L.; Moore, Clinton T.; Dilkina, Bistra; Hepinstall-Cymerman, Jeffrey
Highlights: The problem of Conservation Planning over time by considering spatial connectivity of the selected sites. We propose a multi-period MIP model for the dynamic reserve network design problem. It selects a fully connected subset of sites for a cost-effective conservation. Abstract: The conservation reserve design problem is a challenge to solve because of the spatial and temporal nature of the problem, uncertainties in the decision process, and the possibility of alternative conservation actions for any given land parcel. Conservation agencies tasked with reserve design may benefit from a dynamic decision system that provides tactical guidance for short-term decision opportunities while maintaining focus on a long-term objective of assembling the best set of protected areas possible. To plan cost-effective conservation over time under time-varying action costs and budget, we propose a multi-period mixed integer programming model for the budget-constrained selection of fully connected sites. The objective is to maximize a summed conservation value over all network parcels at the end of the planning horizon. The originality of this work is in achieving full spatial connectivity of the selected sites during the schedule of conservation actions.